Analysis of a car door subjected to side pole impact - Long,C. R. (2019)
Abstract The results of a study on the response of a side impact beam located in a car door to impact loading is presented. The side impact beam is situated in both the front and rear side doors of a vehicle between the inner and outer shells to minimise intrusion into the passenger compartment during a collision whilst absorbing as much impact energy as possible. A numerical model of a light-weight passenger car, developed by the National Crash Analysis Center (NCAC) of The George Washington University under a contract with the Federal Highway Administration (FHWA) and National Highway Traffic Safety Administration (NHTSA) of the United States Department of Transportation (US DOT), was used to simulate a side impact on the front side door using the LS-DYNA R7.1.1 explicit solver. The resulting deformation of the door from the full vehicle model was used to design an experiment for an impact test on a passenger door to validate the simulation of an equivalent numerical model. In the experiments, the car door was subjected to a drop mass of 385 kg from a height of 1.27 m so that the maximum deflection on the car door impact test would be of similar magnitude to the maximum deflection of the door in the simulation of the full car model. Drop test experiments on beams with square and round cross-sections were carried out to validate the equivalent finite element model. The side impact beam was isolated for limited geometric optimisation with a view to improving the crashworthiness of the vehicle. The optimised compound tube configuration performed better than the single tube configuration in terms of SEA (specific energy absorbed) and maximum deflection.